The highest frequency of BRCA1 c.3700_3704del detected among Albanians from Kosovo - Kostovska Maleva, Ivana; Jakovchevska, Simona; Özdemir, Milena Jakimovska; Kiprijanovska, Sanja; Kubelka-Sabit, Katerina; Jasar, Dzengis; Iljovska, Marina; Lazareva, Emilija; Smichkoska, Snezhana; Plasheska Karanfilska, Dijana (Greater Poland Cancer Centre, Poland, 2022)
Background: The spectrum of BRCA1 and BRCA2 mutations varies among populations; however, some mutations may be frequent in particular ethnic groups due to the “founder” effect. The c.3700_3704del mutation was previously described as a recurrent BRCA1 variant in Eastern European countries. This study aimed to investigate the frequency of c.3700_3704del BRCA1 mutation in Albanian breast and ovarian cancer patients from North Macedonia and Kosovo. Materials and methods: A total of 327 patients with invasive breast and/or ovarian cancer (111 Albanian women from North Macedonia and 216 from Kosovo) were screened for 13 recurrent BRCA1/2 mutations. Targeted NGS with a panel of 94 cancer-associated genes including BRCA1 and BRCA2 was performed in a selected group of 118 patients. Results: We have identified 21 BRCA1/2 pathogenic variants, 17 (14 BRCA1 and 3 BRCA2) in patients from Kosovo (7.9%) and 4 (1 BRCA1 and 3 BRCA2) in patients from North Macedonia (3.6%). All BRCA1/2 mutations were found in one patient each, except for c.3700_3704del BRCA1 mutation which was observed in 14 unrelated families, all except one originating from Kosovo. The c.3700_3704del mutation accounts for 93% of BRCA1 mutation positive cases and is present with a frequency of 6% among breast cancer patients from Kosovo. Conclusions: This is the first report of BRCA1/2 mutations among breast and ovarian cancer patients from Kosovo. The finding that BRCA1 c.3700_3704del represents a founder mutation in Kosovo with the highest worldwide reported frequency supports the implementation of fast and low-cost screening protocol, regardless of the family history and even a pilot population-based screening in at-risk population.
Keywords: BRCA1; c.3700_3704del; founder mutation; breast cancer; Kosovo